Annealing Environment Dependence of Solution-Immersion Grown Nickel Oxide Nanoflowers - Parimon, N. (International Journal of Integrated Engineering, 2025)
Herein, nickel oxide (NiO) nanoflowers with improved crystallinity were grown on the NiO seed-coated glass substrates using different annealing environments. An atmosphere of argon (Ar) gas was used during the heat treatment process of the sample and compared with another sample annealed in an ambient atmosphere. The effects on the structural and optical properties of NiO nanoflowers were then investigated. The properties of NiO nanoflowers annealed at 500 °? in an Ar and ambient atmosphere surrounding were analyzed using X-ray diffraction (XRD), field emission scanning electron microscopy, and ultraviolet-visible spectroscopy. The XRD patterns of the highly porous NiO nanoflowers showed they were in a cubic NiO-type polycrystalline structure. The average crystallite sizes estimated from the three most prominent peaks of XRD were quite similar, with 19.0 nm and 19.4 nm for the samples annealed in the ambient and Ar environments, respectively. The dislocation density is slightly higher for the sample annealed in Ar. The optical properties demonstrated that the average transmittance in the visible region was approximately 32% and 37% for the NiO samples annealed in the ambient and Ar environments, respectively. Further, the absorbance spectra showed a higher absorption edge when the sample was annealed in the Ar atmosphere, which is 410 nm compared to 360 nm when annealed in the ambient environment.